The effectiveness of Memrise application on student's English writing in junior high school - Qurrotu'ain, Khumairo; Yuniar, Rendhi Fatrisna (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Indonesian students face various challenges in writing English, especially when composing descriptive texts due to limited vocabulary and low motivation. This study aims at test the effectiveness of the Memrise application in improving students' writing skills in descriptive texts. This study was conducted at SMP Namira, Probolinggo City using a quasi-experimental design with a nonequivalent control group design. This study involved two classes: an experimental class, which used the Memrise application in learning, and a control class, which used quasi-experimental methods. The results showed that the use of Memrise helped students improving their vocabulary, sentence structure, and writing organization. After conducting validity, reliability, normality, and homogeneity tests, it was found that the data met statistical requirements. Hypothesis testing showed that there was a significant difference in students' writing achievement between the experimental and control groups, concluding that Memrise was effective in improving writing performance. Based on these findings, it is recommended for English teachers to utilize the Memrise application as a learning medium to support students' vocabulary and writing development. Future researchers are encouraged to explore the use of Memrise in other English language skills or different educational level.